Dinamika Hubungan Perang dan Kebudayaan: Studi Kasus Pengaruh Perang Terhadap Identitas Bangsa - Faisal Yusman; Alradix Djansena; Yuli Kartiningsih (Mahesa Research Center, 2025)
This study explores how civil wars serve as catalysts for the transformation of military strategy and the shaping of national identity, particularly in the transition from second-generation warfare (2GW) to third-generation warfare (3GW). Using a descriptive qualitative approach and literature analysis from reputable international sources, this research examines the dynamics of combat tactics, the role of non-state actors, and the socio-political impacts of internal armed conflicts. Findings reveal that civil wars promote the adoption of more flexible, adaptive, and decentralized military strategies, such as infiltration, urban warfare, and the use of low-cost yet effective technologies like drones. Moreover, these conflicts generate social pressure, refugee flows, and intergenerational trauma that reconstruct collective identity and national narratives. Civil wars not only trigger tactical innovation within the military domain but also drive significant changes in power structures and the global social landscape. Thus, civil wars function as both strategic arenas and historical laboratories for the evolution of contemporary warfare paradigms.